Protective Effect of Retinoic acid preconditioning on H2O2-induced Apoptosis in Hair Cell-like Cells - Niknazar, Somayeh; Changaee, Naser; Abbaszadeh, Hojjat-Allah; Peyvandi, Maryam; Peyvandi, Ali Asghar (Journal of Otorhinolaryngology and Facial Plastic Surgery, 2022)
Background: Several researches have proven that high levels of noise can induce oxidative stress and increase free radical's formation, particularly hydrogen peroxide (H2O2) and nitric oxide (NO) production. Retinoids are polyisoprenoid lipids derived from vitamin A or retinol. These molecules are essential regulatory elements in cell processes. All-trans retinoic acid (ATRA) plays a vital function in cellular growth, apoptosis, reproduction, cell differentiation, and immune feature by binding to its nuclear receptors. Aim: In this study, we studied the protective effect of ATRA on H2O2-induced damage to bone marrow mesenchymal stem cell (BMSCs)-derived hair cells in culture. Methods: Expression of MATH1 and SOX2 genes were assayed by immunocytochemistry (ICC). In order to evaluate the tolerance of ATRA-treated cells, after incubation of hair cells-like cells with ATRA, it was exposed to H2O2 as an oxidative stress model. Then, the apoptosis percentage of cultivated hair cell-like cells was evaluated by acridin-orange staining method. Results: Our findings revealed that apoptotic cells were markedly diminished in the ATRA +H2O2 co-treated cells in comparison with the H2O2 only–treated group. Conclusion: ATRA has the protective effect against oxidative stress damage in the cultivated hair cells- like cells by reducing the apoptosis.